Optimization of Eggtray Raw Material Mixing Process Using Genetic Algorithm Case Study: PT. Sinar Era Box Gresik - Adi Kriswanto; Syariful Alim; Fardanto Setyatama (Fakultas Teknik Universitas Bhayangkara, 2019)
The rapid development of technology and the increasingly fierce competition between companies in this globalization era, requires that the company's performance runs professionally and appropriately. PT. Sinar Era Box is one of the avalan paper processing company located in Gresik. The company has several divisions, one of which is industrial packing division that uses paper waste such as egg shelves (eggtray). But the company is still less than optimal in the process of mixing eggtray raw materials. So that in the process and the results of its production sometimes experience delays and does not meet market demand. Genetic algorithm is one of algorithm to find solution of combination optimization problem, that is get optimal solution value to a problem having many solution possibilities. From the results of research that has been done has successfully built an Optimization System Process Mixing Raw Material Eggtray using genetic algorithm that can be used to find optimal value solution done mixing process of eggtray raw materials.